The Effect of Repeated Injections of 99mTc-Antimony-Sulphide Colloid on the RES of the Rat — Histopathologic Study - Kazem, I.; Jacobs, H.; Claessens, R.; de Jong, J. (Nuklearmedizin - NuclearMedicine, 1980)
Experiments on inbred albino rats were performed to test the effect of repeated administrations of 99mTc-antimony sulphide colloid on the integrity of the RES. Experiments were carried out in two batches, one with the preformed colloid given in increasing doses, and the other with the labelled colloid in increasing doses. In all, 9 groups of animals including a control group were tested. Studies included: organ weights of liver, spleen, lungs and kidneys, histopatholo- gy, contact macroautoradiography, microautoradiography and 99mTc activity distribution in organs. Results showed no macroscopic or microscopic evidence of tissue damage after repeated injections up to a total dose of 18 mCi 99mTc, 142.2 mg PVP, and 693 μg Sb, given in 9 equivalent doses at one week intervals. It is concluded that repeated administrations of 99mTc-antimony sulphide colloid for liver scintigraphy are safe.